THE EFFECTIVENESS OF USING PICTURE CARD IN WRITING DESCRIPTIVE TEXT - RONA MERITA (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2023)
This research is generally to find out the effectiveness of using picture card in writing descriptive text to the seventh grade students of SMP Wahidiyah Kediri in academic year 2022/2023. The researcher use Quasi-experimental applied in VII A. This research had been done in six meetings, the first meeting is pre-test, four meetings are the treatment, and the last meeting is post-test.The researcher uses quantitative method with analyzed the data by using T-test. The result shows that there is significance different between students are taught by using Picture Card and without Picture Card. The data analysis shows that Tcount > Ttable (2,651 > 1,664), Ha is accepted. In the Pre-test, the average score of VII A class (Experiment Class) is 65 and VII B class (Control Class) is 62. In the Post-test, the average score VIIC class (Experiment Class) is 74 and VIID class (Control Class) is 65. The result shows that the average score of Experiment Class is higher than Control Class in Post-test. Therefore, it can be concluded that Picture Card is effective to teach writing descriptive text.Key words : Writing, Descriptive Text, Picture Card